"All by Myself?" Journalists' Routines and Decision-making in Gathering and Publishing Death-related Visuals. (21st April 2023) - Ivask, Signe; Laak, Brit; Kuulpak, Kadri
ABSTRACT: The purpose of this study was to analyse journalists' routines and decision-making in gathering and publishing death-related visuals. Empirical data were collected by analysing visuals published in two cases: the death of a teen, and a person who had a mental illness. We conducted eight in-depth interviews with people involved in publishing the visuals. The data showed no guidelines in the newsroom of how journalists should act when covering sensitive topics. Although producing or publishing the visuals depended on various beliefs and professional norms of people involved, the reporter as the last link in the chain had to take responsibility for the visuals. Yet, reporters usually did not get to choose how the visuals were produced. The lack of instructions and internal agreements led to relying on routines that did not consider the ethical aspects of covering sensitive topics.